(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Nowadays, the best alternative to fossil fuel-based power plants is solar PV power generation.The development of the aforementioned will undoubtedly lead to the retirement of thermal and nuclear power plants in the future.In comparison to other renewable energy sources currently available, it is rapidly developing globally, and the costs of production and installation are decreasing.This study compares an improved PV solar power system design with an MPPT controller to existing methods that coped with fluctuating sun irradiation, unprotected areas, and partial shadowing. Design stage and maintenance procedure will be aided by this for maintenance directors and designers.